2013
DOI: 10.1186/2049-1891-4-28
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes cell proliferation by modulating E2F1 in chicken pulmonary arterial smooth muscle cells

Abstract: In this study, we sought to investigate the expression of the transcription factor E2F1 in chicken pulmonary arterial smooth muscle cells upon hypoxia exposure, as well as the role that E2F1 played in the regulation of cell proliferation. Isolated chicken pulmonary arterial smooth muscle cells were subjected to hypoxia or normoxia for indicated time points. Cell viability, DNA synthesis, cell cycle profile, and expression of E2F1 were analyzed. The results showed that hypoxia promoted cell proliferation and DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Pulmonary vascular remodeling was confirmed as an important pathological contributor to AS that leads to an increase in pulmonary vascular resistance, prolonging elevated arterial hypertension [ 24 ]. Among vascular well cells, the proliferation and hypertrophy of vascular smooth muscle cells was thought to be a main contributor that facilitates pulmonary vascular remodeling and has an important role in AS progression [ 57 , 58 ], this was in accord with the current changes in this study. Comprehensively, the pathological changes further supported the present RNA-seq findings in the pulmonary arteries from broilers with or without AS, and we revealed some specific components of complex molecular circuitry regulating pulmonary artery remodeling underlying in AS progression.…”
Section: Discussionsupporting
confidence: 83%
“…Pulmonary vascular remodeling was confirmed as an important pathological contributor to AS that leads to an increase in pulmonary vascular resistance, prolonging elevated arterial hypertension [ 24 ]. Among vascular well cells, the proliferation and hypertrophy of vascular smooth muscle cells was thought to be a main contributor that facilitates pulmonary vascular remodeling and has an important role in AS progression [ 57 , 58 ], this was in accord with the current changes in this study. Comprehensively, the pathological changes further supported the present RNA-seq findings in the pulmonary arteries from broilers with or without AS, and we revealed some specific components of complex molecular circuitry regulating pulmonary artery remodeling underlying in AS progression.…”
Section: Discussionsupporting
confidence: 83%
“…This was of particular interest to us given recent reports alluding to the presence of abnormalities in the DNA repair machinery found in both pulmonary endothelial (40) and smooth muscle cells (41) from patients with IPAH. Furthermore, TopBP1 has been shown to interact with E2F1 (42), a gene reported to promote pulmonary smooth muscle cell proliferation in the setting of hypoxia (43,44). In our patient population, we found three singlenucleotide variants (SNVs) (Figure 2A) located in close proximity to both the TopBP1 transactivation domain (rs55633281) and the topoisomerase II interacting domain (rs17301766 and rs10935070) ( Figure 2B).…”
Section: Relevance Of Top Three Wes Hits To Ipah Pathobiologymentioning
confidence: 83%
“…It has been demonstrated that hMSC at 20% O 2 exhibited significantly increased oxidative stress, DNA damage markers, and telomere shortening rates, compared with cells grown at 3% O 2 [15]. Conversely, numerous studies have demonstrated that ASCs under hypoxia showed the greater number of cells and shorter population doubling time, and oxygen tension as low as 2% had the greatest impact on cell growth [16][17][18]. For clinical applications, stem cells must be sufficiently expanded.…”
Section: Stem Cell Proliferation In Vitromentioning
confidence: 99%